The THE DETERMINANT FACTORS OF ENTREPRENEURIAL ORIENTATION IN EMBROIDERY SMALL ENTERPRISES IN ACEH, INDONESIA - kusdiarni, yuli (Archives of Business Research, 2019)
The entrepreneurial orientation owned by embroidery enterpreneurs is influenced by many factors. Some of these factors include personal creativity, internal environment, external environment and stakeholders. For this reason, this research aims at testing empirically and analyzing the influence of personal creativity, internal environment, external environment and stakeholders on entrepreneurial orientation. This research covers 7 regencies/municipalities in Aceh Province. 200 embroidery enterpreneursare proportionally sampled from these 7 regions for this research. The research results indicate that personal creativity, internal environment, external environment and stakeholders have influence on entrepreneurial orientation.